Main plenary session "Moving towards technological leadership – national projects of technological sovereignty for healthcare" - article Editorial (Разработка и регистрация лекарственных средств)
On October 7, 2024, within the framework of the BIOTECHMED forum, the main plenary session "Movement towards technological leadership – national projects of technological sovereignty for healthcare" was held.